2016
DOI: 10.3389/fnins.2016.00370
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Tinnitus Framework: A Neurofunctional Model

Abstract: Subjective tinnitus is the conscious (attended) awareness perception of sound in the absence of an external source and can be classified as an auditory phantom perception. Earlier literature establishes three distinct states of conscious perception as unattended, attended, and attended awareness conscious perception. The current tinnitus development models depend on the role of external events congruently paired with the causal physical events that precipitate the phantom perception. We propose a novel Neurofu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 98 publications
2
50
0
Order By: Relevance
“…According to the signal-detection model 27 , personality traits can manipulate the response criterion placement so that individuals with increased awareness report even very low levels of signal as tinnitus. This theory is in line with the Jastreboff model 17 , 28 . Durai and Searchfield found that personality traits or psychiatric disorders were not likely to cause tinnitus but more likely to affect how individuals with tinnitus were distressed by amplifying symptoms and complaints 26 .…”
Section: Discussionsupporting
confidence: 87%
“…According to the signal-detection model 27 , personality traits can manipulate the response criterion placement so that individuals with increased awareness report even very low levels of signal as tinnitus. This theory is in line with the Jastreboff model 17 , 28 . Durai and Searchfield found that personality traits or psychiatric disorders were not likely to cause tinnitus but more likely to affect how individuals with tinnitus were distressed by amplifying symptoms and complaints 26 .…”
Section: Discussionsupporting
confidence: 87%
“…32 33 The current consensus is that tinnitus symptoms have multiple etiologies. 34 As such, tinnitus might be related to not only dysfunction of the inner ear or auditory nerves but also to cognitive distortions of somatic sensations. 6 34 Our findings further support the notion that auditory factors (i.e., hearing loss) are associated with the acoustical symptoms (awareness and loudness), whereas psychological traits (anxiety sensitivity) are linked with the non-auditory symptoms (annoyance, impact on life and tinnitus-related handicap).…”
Section: Discussionmentioning
confidence: 99%
“…These neuroanatomical changes play a specific role in both tinnitusrelated emotional state disorder and cognitive deficits (Araneda et al, 2015;Kraus & Canlon, 2012;Simonetti & Oiticica, 2015;Vanneste et al, 2016). Thus, tinnitus-related emotional state disorder (distress and depression) has exhibited a close relationship with tinnitus and cognitive deficits (Ghodratitoostani et al, 2016;Tegg-Quinn, Bennett, Eikelboom, & Baguley, 2016). At the same time, patients with poor cognitive skills may be more likely to harbor misconception about tinnitus, which in turn may lead to clinical symptoms such as fear, anxiety, insomnia, and other harmful psychological reactions.…”
Section: F I G U R E 3 Correlation Analysis Scatterplot Between Tinnitusmentioning
confidence: 99%